Warning and Nursing Experience of Anesthesia Depth Monitoring for Patients with General Anesthesia Delayed to Leave Anesthesia Recovery Room and Delirium - Hongmei Xuan; Keping Xu (Emergency Medicine International)
Affected by the residues of narcotic drugs, patients under general anesthesia are vulnerable to emergence of agitation, delirium, hemodynamic changes, and other adverse events in the recovery period of anesthesia. Therefore, it is necessary to strengthen the observation and care of these patients. Depth of anesthesia monitoring (DAM) has always been a concern for anesthesiologists, but there are few reports related to it. This study compared the early warning value of DAM for patients under general anesthesia with delayed exit from the anesthesia recovery unit (PACU) and delirium and summarized the related nursing experience. The results showed that DAM could reduce the incidence of complications in patients under general anesthesia, reduce the incidence of delirium, shorten the time of postoperative anesthesia recovery and PACU observation time, reduce the workload of nursing staff, and improve nursing satisfaction. DAM plays an important role in improving the quality and efficiency of care in PACU.